2021
DOI: 10.3390/jof7050390
|View full text |Cite|
|
Sign up to set email alerts
|

Epichloë gansuensis Increases the Tolerance of Achnatherum inebrians to Low-P Stress by Modulating Amino Acids Metabolism and Phosphorus Utilization Efficiency

Abstract: In the long-term evolutionary process, Achnatherum inebrians and seed-borne endophytic fungi, Epichloë gansuensis, formed a mutually beneficial symbiosis relationship, and Epichloë gansuensis has an important biological role in improving the tolerance of host grasses to abiotic stress. In this work, we first assessed the effects of Epichloë gansuensis on dry weight, the content of C, N, P and metal ions, and metabolic pathway of amino acids, and phosphorus utilization efficiency (PUE) of Achnatherum inebrians … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 60 publications
0
28
0
Order By: Relevance
“…These have also been shown to be produced in higher amounts in the shoots and roots of E+ grasses and can therefore also alter the microbial population [183]. Endophyte infection upregulates the production of other substances that have physiological implications such as amino acids and sugars [62,65]. We see this particularly under drought and salt stress where some of these substances have osmoregulatory properties.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…These have also been shown to be produced in higher amounts in the shoots and roots of E+ grasses and can therefore also alter the microbial population [183]. Endophyte infection upregulates the production of other substances that have physiological implications such as amino acids and sugars [62,65]. We see this particularly under drought and salt stress where some of these substances have osmoregulatory properties.…”
Section: Discussionmentioning
confidence: 94%
“…A variety of studies have shown Epichloe infected grasses could be more tolerant to low nutrient inputs [59][60][61][62].…”
Section: Low Nutrientsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the original article [1], the wrong "Figure 2a,b" were uploaded due to author's negligence, there were mistakes in "Figure 2a,b" as published. The corrected "Figure 2a,b" appears below, and the corresponding detailed content have also been corrected.…”
Section: Error In Figurementioning
confidence: 99%